Evaluation of quality of life in chronic disease patients - Damjanović, Maja; Kovačević, Milena; Musić, Nina; Vezmar Kovačević, Sandra; Miljković, Branislava (Archives of Pharmacy, 2022)
Quality of life (QoL) has become an important aspect of the therapy outcomes assessment in research and daily practice. The aim was to assess the quality of life in relation to the characteristics of patients or therapy. The study included adult patients (≥18 years) with at least one chronic disease. The Euro-Qol 5D-5L questionnaire was used to assess QoL. Statistical analysis was performed using SPSS software (ver 27). The analysis included 193 patients, mostly women (72%), with mean age 53.7 ± 17.3 years (range 21-91). Polypharmacy (≥5 drugs) was present in 23.4%, and polymorbidity (≥3 diseases) in 19.2% of patients. The most common were diseases of the circulatory system (54.9%), endocrine, nutritional or metabolic diseases (36.3%) and diseases of the musculoskeletal system (20.2%). Good disease control was self-reported by 68.4%. The mean QoL value was 71.1±18.6 (range 7-100). A certain degree of mobility problems was reported by 46.1%, self-care 5.7%, usual activities 36.3%, pain or discomfort 58%, anxiety or depressive feelings 46.9%. The QoL value was significantly higher in patients who stated good disease control (p=0.006), while it was significantly lower in patients with polypharmacy or polymorbidities (both p